MEDIA DEVELOPMENT VIDEO TUTORIAL ON BASIC BADMINTON TECHNIQUES IN HIGH SCHOOLS - Sirait, Muhammad Alvi Fahrezi; Nasution, Usman (Journal of Physical Education, Health and Sports Recreation, 2024)
The aim of this research is to determine the development of video tutorial media for basic badminton techniques in high schools. The method used is the Research and Development (R&D) method with a population of 110 students and the sample in this research is a small group test of 20 students at SMA Negeri 3 Tanjungbalai and a large group test of 90 students at 3 high school level schools. consisting of SMA Negeri 1 Tanjungbalai, SMA Negeri 3 Tanjungbalai and SMA Negeri 6 Tanjungbalai. The data collection technique in this research uses questionnaires given to experts and students. The data analysis technique used is a mixed data analysis technique (qualitative and quantitative). The percentage for knowing the needs analysis is 39%, where the validation percentage assessment by expert Sudjana (2005: 46-47) means that the average validation value is in the range of 29% - 46% with a poor category. The validity percentage for the small group test is 67% and according to expert Sudjana's (2005: 46-47) validation percentage assessment, the average validation value is in the range of 65% - 82% with a good category for use in the large group test stage after improvement. Where the validity percentage for the large group test is 88% and the average validation value is in the range of 83% - 100%, indicating that in the very good category, the development of video tutorial media for basic badminton techniques in high schools is running effectively and efficiently. The results of the small group test involving 20 students at SMA Negeri 3 Tanjungbalai had a percentage result with a score of 78% in the good category and the results of the large group test involving 90 students at the high school level consisting of 30 students at SMA Negeri 1 Tanjungbalai were 90% in the very good category. , 30 students at SMA Negeri 3 Tanjungbalai 89% in the very good category and 30 students at SMA Negeri 6 Tanjungbalai 89% in the very good category. Based on the results of the trials and the results of the researchers' discussions, it can be concluded that the development of video tutorials on basic techniques for playing badminton in high schools is a new breakthrough in the world of physical education, which includes learning material for the sport of badminton. From the results of expert questionnaires on needs analysis, small trials and large trials, it is stated that the development of learning media for video tutorials on basic badminton game techniques is very suitable for use in PJOK learning, especially badminton material. Hopefully in the future the development of learning media will be more numerous and more creative than This.